Utilization of Disposable Diaper Waste with Added Naphthalene Formaldehyde Sulfonate into Paving Blocks in an Effort to Minimize Waste to Reduce Environmental Pollution - Mayang Sari Juita; Dodit Ardiatma; Nur Ilman Ilyas (GoAcademica Research & Publishing, 2023)
This research aims to determine the best classification and composition of paving blocks mixed with baby diaper waste in terms of compressive strength and water absorption of paving blocks based on SNI 03-0691-1996, the effect of variations in baby diaper waste on compressive strength and water absorption tests and to determine the quality comparison. paving blocks mixed with baby diaper waste and commercial paving blocks. The method used in this research is an experimental method, using a quantitative approach. The materials used to produce paving blocks are cement, sand, water, a mixture of baby diaper waste and the added ingredient sikacim concrete additive. The samples were tested to determine the relationship between physical characteristics and mechanical properties with material composition in accordance with the quality of Paving Blocks produced based on SNI 03-0691-1996. In this research, it was determined based on the planning ratio between cement and sand, namely 3:7. Baby diaper waste added to the paving blocks was 0 grams, 5 grams, 10 grams, 15 grams and 20 grams. The best classification and composition for adding baby diaper waste to paving blocks if viewed from the compressive strength of paving blocks is by adding 10 grams of baby diaper waste with a compressive strength of 36.76 Mpa which meets the SNI 03-0691-1996 quality classification A, where this paving block can be used for roads, container terminal land pavement at ports, non-structural and structural needs with other heavy loads. Meanwhile, if we look at the water absorption capacity of the paving blocks, the best classification and composition of adding 5 grams of baby diaper waste with the lowest water absorption capacity of 1.41% meets the SNI 03-0691-1996 quality classification standard A.